L’héritage paysager pour penser la transition écoclimatique d’un vignoble - Myriam Laidet; Patrick Moquay; Isabelle La Jeunesse (Projets de Paysage)
This article looks at the cultural landscape of Savennières (in the urban area of Angers, a Unesco World Heritage site in the Loire Valley), which is characterised by a high density of wine-growing châteaux and landscaped parks. It is also a vineyard region with a strong commitment to organic farming. An appellation strategy is envisaged to maintain the balance of the winegrowing ecosystem threatened by climate change and to assert the winegrowing identity disrupted by the suburbanisation of the city of Angers. In a context of ecological and climatic transition, how can the future of this vineyard be considered thanks to the landscape? The research method is both historical (diachronic analysis of heritage and landscape) and sensitive (observation trail, analysis of perceptions and representations). The aim is to characterise the cultural value of the vineyard through expertise and dialogue at the level of the territory. The aim is to explore a new relationship to the landscape, combining ethics and aesthetics at the service of an agroecological viticultural approach.